Effects of fatigue on inter-cycle variability in cross-country skiing - Cignett, F.; Schena, F.; Rouard, A. (Journal of Biomechanics, 2009)
The aim of the study was to examine the inter-cycle variability in cross-country skiing gait and its evolution with fatigue. Both issues were investigated to understand the flexibility capabilities of the neuromuscular system. Four women and four men skied on a treadmill, up to exhaustion. The angular displacements of the arms and legs movements were obtained for 40 s period at the beginning and end of the skiing test. Mean inter-cycle standard deviation (SDc), largest Lyapunov exponent (l1) and correlation dimension (Dc) were computed for each time series and surrogate counterpart to evaluate the magnitude and nature of the variability. For any experimental time series, l1 was positive, Dc greater than 1 and both were found to be different from their surrogate counterparts, confirming that the temporal variations of the data had a deterministic origin. More, larger SDc, Dc and l1 values were observed at the end of the test, indicating more variability, noise and local dynamic instability in the data with fatigue. Hence, the fluctuations of limb angular displacements displayed a chaotic behavior, which reflected flexibility of the neuromuscular system to adapt to possible perturbations during skiing. However, such chaotic behavior degraded with fatigue, making the neuromuscular system less adaptable and more unstable.